Perancangan Model Strategi Digital Marketing pada Keripik Nanas Usaha Baru Ibu di Kabupaten Kampar dengan Pendekatan Grounded Theory - Putra, Yudhy Soneta; Yulianto, Ardhian Agung; Hasan, Alizar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Micro, small, and medium enterprises (MSMEs) contribute significantly to national economic growth, yet they still face challenges in expanding their markets. One of the main obstacles is the reliance on conventional promotion methods and the limited use of digital media. This study aims to design a digital marketing strategy model for “Usaha Baru Ibu,” a pineapple chips producer in Kampar Regency, Riau, using the Grounded Theory approach. This qualitative study involved observation, in-depth interviews with business owners, competitors, and consumers, as well as documentation. Data analysis was carried out through open coding, axial coding, and selective coding. The findings revealed 15 variables influencing digital marketing strategies, with seven core variables identified as the most crucial: technological availability, capability, supporting infrastructure, human resource readiness, product uniqueness, customer expectations, and customer social media. A new theory emerged stating that the success of MSMEs’ digital marketing depends on technological readiness, human resource capability, social media utilization, and the delivery of product uniqueness aligned with customer expectations.